Pemetaan Portofolio Optimal dalam Manajemen Kekayaan pada Investasi Saham : Studi Bibliometrik VOSviewer dan Literature Review - Doni Yusuf Bagaskara; Rohmadi; Yuniarti Hidayah Suyoso Putra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to determine the mapping of research around optimal portfolios in wealth management on stock investment with a mix-method approach, namely VOSviewer bibliometric studies and literature reviews. “Data analysis techniques include: (1) mapping the number of journal publications spread around the Optimal Portfolio using Microsoft Excel and Mendeley Desktop by year of publication; (2) mapping the results of bibliometric network visualization and journal publication trends around the Optimal Portfolio using VOSviewer (Visualization of Similarities) algorithm software based on the number of clusters and their items; and (3) map research topics around the Optimal Portfolio using literature studies. The results showed that: (1) based on mapping the number of journal publications, there were 500 journal publications around the optimal portfolio; (2) based on the mapping of VOSviewer bibliometric studies The results of network visualization around the optimal portfolio are divided into 6 clusters and 163 topic items; (3) Based on the mapping of literature review studies, there are 2 topics around optimal portfolios that often appear first optimal and second stocks. The implication and contribution of this study is to map research topics around optimal portfolios in stock investments that are often or rarely researched by researchers, so that they can be a reference for researchers afterwards”.